2016
DOI: 10.1038/ncb3436
|View full text |Cite
|
Sign up to set email alerts
|

SCAI promotes DNA double-strand break repair in distinct chromosomal contexts

Abstract: Summary DNA double-strand breaks (DSBs) are highly cytotoxic DNA lesions, whose accurate repair by non-homologous end-joining (NHEJ) or homologous recombination (HR) is crucial for genome integrity and is strongly influenced by the local chromatin environment. Here, we identify SCAI (Suppressor of Cancer Cell Invasion) as a 53BP1-interacting chromatin-associated protein that promotes the functionality of several DSB repair pathways in mammalian cells. SCAI undergoes prominent enrichment at DSB sites through du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 51 publications
7
44
0
Order By: Relevance
“…Among the multiple repair pathways and processes involving SCAI shown by Hansen et al (2016), our study suggests a 53BP1-dependent function in the regulation of BRCA1-mediated repair pathways, possibly including alt-NHEJ and resectiondependent NHEJ in G1, as well as HDR in S/G2, by counteracting RIF1. It will be interesting to determine the 53BP1-independent function and regulation of SCAI.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Among the multiple repair pathways and processes involving SCAI shown by Hansen et al (2016), our study suggests a 53BP1-dependent function in the regulation of BRCA1-mediated repair pathways, possibly including alt-NHEJ and resectiondependent NHEJ in G1, as well as HDR in S/G2, by counteracting RIF1. It will be interesting to determine the 53BP1-independent function and regulation of SCAI.…”
Section: Discussionmentioning
confidence: 73%
“…There are some contradictory results between the current analyses and Hansen et al (2016)'s study, including the effect of SCAI depletion on Rad51 foci formation and the HDR reporter assay. Time course analysis revealed that Rad51 foci in S/G2 cells were significantly affected by SCAI depletion at earlier (0.5-1 hr) time points after irradiation, but not at the later (3 hr) time point used by Hansen et al (2016), implying a positive role for SCAI in HDR. The reason for the different HDR reporter assay results in the two studies remains unknown; however, the effect may differ in stable knockout (chronic SCAI depletion) and transient knockdown (acute SCAI depletion) cells.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Whereas 53BP1-RIF1 promotes certain NHEJ events, 53BP1 bound to SCAI seems to be competent for HR, potentially representing a way in which the balance of repair pathways can be altered. Many HR factors are essential for embryonic development, whereas Scai Ϫ/Ϫ mice are viable but show a defect in 53BP1-dependent repair of heterochromatic DSBs (73). Clearly further work is required to fully understand the role of SCAI in DSB repair.…”
Section: Repair Regulation Downstream Of 53bp1mentioning
confidence: 99%